2014
DOI: 10.1002/pd.4332
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of chromosomal mosaicism in over 1600 cases using array comparative genomic hybridization as a first line test

Abstract: This study demonstrates that the use of aCGH as a first line test is able to identify chromosomal mosaicism down to 9%, which is lower than the level reliably detected using standard cytogenetic analysis. aCGH avoids the disadvantages of culturing, which include culture bias, artifact, and culture failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 39 publications
6
22
2
Order By: Relevance
“…Confined placental mosaicism detected at prenatal diagnosis using CVS is a well‐documented phenomenon. Chromosome analysis by traditional karyotyping is reported to have mosaicism detected in 1% to 2% of first trimester pregnancies, and the detection rate using microarray is quite comparable . Similarly, in this study, we observed mosaicism in 3.0% (42 out of 1382) of the CVS cases using CMA.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Confined placental mosaicism detected at prenatal diagnosis using CVS is a well‐documented phenomenon. Chromosome analysis by traditional karyotyping is reported to have mosaicism detected in 1% to 2% of first trimester pregnancies, and the detection rate using microarray is quite comparable . Similarly, in this study, we observed mosaicism in 3.0% (42 out of 1382) of the CVS cases using CMA.…”
Section: Discussioncontrasting
confidence: 82%
“…Chromosomal microarray analysis significantly increases the diagnostic yield compared with conventional karyotyping yet without significantly increasing the frequency of detecting variants of unknown significance . In addition, it has been demonstrated to be a powerful tool to detect mosaicism at levels as low as 9% . However, while cytogenetic analysis of the cytotrophoblast layer of CVS tissue is no longer conducted in many laboratories, primarily because of the labor‐intensive procedure of requiring both short‐ and long‐term cultures, microarrays are frequently performed on intact CVS tissue that includes this outer cell layer.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our results, and in agreement with recently published data [45,46], we can conclude that aCGH performed on directly extracted DNA is in fact equally suited, if not superior, to routine karyotype for the detection of low level mosaic aneuploidy, bearing in mind that classic karyotype analysis must examine at least 20 metaphases in order to reliably detect the presence of mosaicism at a level of ≥15%, which is not routine practice in PCD (typically 16 metaphases are counted).…”
Section: Resultssupporting
confidence: 83%
“…It was once reported as 65% and 70% during the early mitotic stage [41, 42], and as 10% during the blastocyst stage [4]. The chromosomal mosaicism was also observed in the prenatal tests of non-IVF people, including chorionic villus (about 1.78%) and amniotic fluid (about 0.46%) [43]. The propagation of abnormal cell line(s) in the mosaic embryos had negative effect in the pregnancy, and the undetected mosaicism and aneuploidies in the PGS/aCGH was recently reported as a cause to the first trimester pregnancy loss [44].…”
Section: Discussionmentioning
confidence: 99%